The Influence of Cash Flow Management, Product Planning, and Financial Technology Adoption on the Financial Performance of MSMEs in Bandar Lampung City - Serly Setiyani; Lestari Wuryanti; Muhammad Irfan Pratama (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of cash flow management, product planning, and financial technology adoption on the financial performance of Culinary MSMEs in Bandar Lampung City. This study uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to Culinary MSME actors and analyzed using multiple linear regression analysis with the help of the SPSS program. The results of the study show that partially cash flow management, product planning, and the adoption of financial technology have a positive and significant effect on the financial performance of Culinary MSMEs. Simultaneously, the three independent variables also have a significant effect on the financial performance of Culinary MSMEs. The results of the determination test showed that cash flow management, product planning, and financial technology adoption were able to explain the variation in the financial performance of Culinary MSMEs by 77.4%, while the rest was influenced by other factors outside of this study. The results of this study are expected to be a consideration for Culinary MSME actors in improving financial performance through good cash flow management, proper product planning, and optimal use of financial technology.